The wings of darkness and other cases eaudiobook - Simon, Seymour (Einstein Anderson, 2001)
Sixth-grader Adam "Einstein" Anderson is a true science detective. He can solve just about any mystery, even when everybody else is fooled. He also tries to make people laugh by telling bad jokes-but they usually groan instead. All sorts of people test Einstein's scientific knowledge. A man working on a horror movie claims he's seen a real vampire, but Einstein isn't so sure. Margaret, Einstein's best friend, has a photograph of an anti-gravity machine. Does Einstein think the photo is a fake? Pat, the class bully, needs Einstein's help to win a contest. Pat wonders if it is easier to fold a newspaper in half nine times or push a plastic straw through a raw potato. Einstein knows. Author Seymour Simon bases Einstein's adventures on his own childhood and his former career as a science teacher. Johnny Heller reads this collection of 10 witty stories with youthful energy and spirit.